2011
DOI: 10.1111/j.1365-2265.2011.04001.x
|View full text |Cite
|
Sign up to set email alerts
|

Hair cortisol content in patients with adrenal insufficiency on hydrocortisone replacement therapy

Abstract: Hair cortisol content correlates with hydrocortisone (HC) dose in patients with AI. Our results suggest that some AI patients may be over-treated and hence may be at risk for the adverse effects of cortisol. Measurement of HC in hair may become a useful monitoring tool for long-term cortisol exposure in patients treated with glucocorticoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 33 publications
(72 reference statements)
2
28
0
Order By: Relevance
“…Recently, its clinical application has expanded as a monitoring tool for drug therapy [14,15] or for biomarker studies for disease [16] and alcohol addiction [17]. Since anorectics have high abuse potential, their abuse can be proved by segmental hair analysis along with individual prescription records in forensic and clinical areas.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, its clinical application has expanded as a monitoring tool for drug therapy [14,15] or for biomarker studies for disease [16] and alcohol addiction [17]. Since anorectics have high abuse potential, their abuse can be proved by segmental hair analysis along with individual prescription records in forensic and clinical areas.…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported higher mean HCC in hydrocortisone-treated patients compared to healthy individuals or non-AI controls. In the two studies performed in adult AI patients, (19,20), while in the other two studies, HCC correlated significantly with BMI but not with hydrocortisone dose (21,22). In the adrenocortical carcinoma patients, this can be explained by mitotane treatment, which alters the metabolism of hydrocortisone.…”
Section: Hydrocortisone Replacement Therapy Monitoringmentioning
confidence: 90%
“…Several published studies have investigated HCC in patients treated with hydrocortisone for AI. The studies included 132 adults with AI, 93 adults with AI, 54 children with AI and 15 adults who were treated with the adrenolytic drug mitotane for adrenocortical carcinoma (19,20,21,22). All studies reported higher mean HCC in hydrocortisone-treated patients compared to healthy individuals or non-AI controls.…”
Section: Hydrocortisone Replacement Therapy Monitoringmentioning
confidence: 99%
“…Conversely, Thomson et al showed great variability in salivary cortisol in a crossover study of 27 patients being treated with hydrocortisone (oral or IV), and did not show a good correlation between plasma and saliva levels, making it difficult to employ in current practice [51]; • cortisol in hair: hair growth (1 cm per month) and the correlation between cortisol level in the hair and exposure to glucocorticoids could allow detection of overdose or underdosage in patients with adrenal insufficiency. A pilot study showed no significant difference between patients and female control subjects, but a difference was observed between male subjects [52]; • plasma ACTH: plasma ACTH does not assist in evaluating glucocorticoid replacement therapy with classic rapid release hydrocortisone since ACTH is always high in the morning on waking and then decreases rapidly after administration of hydrocortisone in primary adrenal insufficiency [53]. In the study by Rousseau et al, the amplitude of the fall in ACTH after the morning administration of hydrocortisone correlated less well with area under the curve for cortisol than cortisol measured at the morning peak of 10 am [49].…”
Section: Adult Patientsmentioning
confidence: 88%